Mobile and wireless networks - Al Agha, Khaldoun; Pujolle, G., 1949-; Ali-Yahiya, Tara (Advanced networks set ;, 2016)
A cellular network or mobile network is a wireless network distributed over land areas called cells, each served by at least one fixed-location transceiver, known as a cell site or base station. In a cellular network, each cell uses a different set of frequencies from neighboring cells, to avoid interference and provide guaranteed bandwidth within each cell. This book explores the benefits of cellular networks across a range of applications.